1992
DOI: 10.1111/j.1600-051x.1992.tb00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Listerine®, Meridol® and chlorhexidine mouthrinses as supplements to regular tooth‐cleaning measures

Abstract: The anti-plaque, anti-gingivitis and anti-microbial efficacies of a phenolic compound (Listerine) and 2 different amine/stannous fluoride mouthwashes (Meridol I, II) were compared when these solutions were used in addition to usual tooth cleaning. A placebo preparation was utilized as a negative control and a chlorhexidine solution as a positive control in this double-blind study. After professional tooth cleaning, 49 volunteers continued their habitual, self-performed and non-supervised oral hygiene for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 9 publications
11
78
1
4
Order By: Relevance
“…The subjects usually would improve their oral hygiene although they did not have the knowledge of the regimen administered to them. This was in agreement to another study by Brecx et.al (13) comparing the efficacy of Listerine, Meridol and Chlorhexidine on plaque and gingivitis, where it was demonstrated that mean PI scores in the placebo group decreased at day 7 due to the Hawthorne effect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The subjects usually would improve their oral hygiene although they did not have the knowledge of the regimen administered to them. This was in agreement to another study by Brecx et.al (13) comparing the efficacy of Listerine, Meridol and Chlorhexidine on plaque and gingivitis, where it was demonstrated that mean PI scores in the placebo group decreased at day 7 due to the Hawthorne effect.…”
Section: Discussionsupporting
confidence: 92%
“…These side effects are brown discolouration of the teeth and tongue, oral mucosal erosion and taste perturbation (12). Several side-effects associated with its use have stimulated the search for new chlorhexidine solutions with various concentrations and flavoring agents, as well as alternative anti-plaque agents (13).…”
Section: Introductionmentioning
confidence: 99%
“…Among various oral rinses, chlorhexidine is coupled to hydroxyapatite, brown pellicle and the plague and inhibits growth of bacteria by being activated by gradation for 12 to 24 hours when coupled to hydroxyapatite 7) . Weitz et al 8) argued that using 0.12% of chlorhexidine for toothbrushing reduced the plague and Brecx et al 9) reported that chlorhexidine and meridol were most effective in inhibiting the plague after comparing the inhibitory effects of listerine, a phenolic substance and meridol and chlorhexidine, solutions containing fluorinated amines. However, the long-term use leads to side effects such as tolerance 10) .…”
Section: Sung-im Kim Et Al:antimicrobial Effect Of Oral Rinses and Nmentioning
confidence: 99%
“…The use of topical antibacterial agents to help reduce bacterial plaque may be beneficial for the prevention and treatment of gingivitis in some patients [54][55][56].…”
Section: Professional and Home Care For Gingival Healthmentioning
confidence: 99%
“…Active ingredients in the other two are chlorhexidine digluconate and triclosan [55]. If properly used, the addition of a topical anti-plaque agent to a gingivitis treatment regimen for patients with deficient plaque control will likely result in reduction of gingivitis [56]. However, experimental evidence indicates that penetration of topically applied agents into the gingival crevice is minimal [57].…”
Section: Professional and Home Care For Gingival Healthmentioning
confidence: 99%